A SYSTEMATIC LITERATURE MAPPING ON SECURE IDENTITY MANAGEMENT USING BLOCKCHAIN TECHNOLOGY - Ishaq Azhar Mohammed (International Journal of Innovations in Engineering Research and Technology, 2019)
Although a safe exchange of information, services, and technologies are possible via centralized digital organizations, there are significant concerns associated with the digital revolution. Without the users’ knowledge or permission, telecommunications companies gather and absorb information that is utilized for data analysis, profiling, and exploiting purposes by third parties [1]. The continuation of service providers’ centered solutions is wasteful due to duplication, it has significant security flaws, and it is burdensome for consumers. To accomplish the security and privacy of dispersed digital identities, it is necessary to authenticate and verify the digital individual’s identity [1]. Nevertheless, thorough research on the elements of identity management, as well as user data protection and privacy measures in the identity management system, is still lacking in the published studies, according to the researchers [1,2]. Managing and verifying digital identities is undoubtedly among the most important applications of blockchain technology for various developments. Throughout 2018, millions of individuals all around the globe were affected by data breaches involving their personal information. It is necessary to develop more secure methods of storing, exchanging, and validating sensitive material. In this respect, developing blockchain solutions for identification systems may help address some of the issues experienced by most centralized databases.